Increased Productivity through Adaptive Behavior, Work Environment, and Training - Indraswari, Isna Tianafitri; Martono, S (Universitas Negeri Semarang, 2020)
This study aims to examine the relationship between adaptive behavior, work environment, training, and employee productivity. The sample for this study consisted of 235 employees of PT. Djarum Brak Sekarjati Jepara calculated using the purposive random sampling method. Data collection methods using the questionnaire method which is measured using a Likert scale. Regression analysis showed that there is a positive influence between adaptive behavior with employee productivity, there is a posisitif influence between the working environment and employee productivity, and a positive influence between training and employee productivity. Based on these results meal can be interpreted that the employees of PT. Djarum Brak Sekarjati has good adaptive behavior. This is supported by the environment and good training provided by the company to employees.